Construire des salles de cinéma durant les Trente Glorieuses : le cas méconnu de l’architecte Georges Peynet - Andrés Avila Gómez (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
While some architectures produced during the "Glorious Thirty" have been the subject of extensive research, others remain neglected by the historiography of architecture recently written in France. This is the case of architectures designed for cinematographic exploitation, whose research and publications devoted to their evolution (Meusy; Abadie) have so far specifically addressed the periods of its birth (1895-1918) and development (between the wars), without examining the intense theatre construction activity since the Reconstruction.In this context, and based fundamentally on the analysis of architectural and film periodicals of the time, our text presents a first approach to the figure of the most prolific theatre designer in France from the 1940s to the 1970s: Georges Peynet. The study of this architect's career highlights the presence in France of an elite group of designers specialising in cinema architecture, unknown in architectural circles but widely recognised and in demand among cinema operators.As the leading French "cinema architect", Peynet has forged a career exclusively dedicated to the design of cinemas, contributing to the transformation of this architectural program.